(3GdebOeI GdCLQhejI aj Yde GdYQHjIs - (3GdUfgGLj, GHf BLQhe, CHh YHO Gddg, eMeO Hf YHO Gddg Hf OGhO, (B723 (3g`s
(3ChdgG (B:s
(3GdcdGe gh GddaX GdeQcH GdeajO HGdhVYs
(3BNQgG (B:s
(3hGdPj jbOQ Hef fMh KhH NR hHGH SGL hNGJe aVIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 33s
(3eYLe GdeDdajf(B: 3 / 641s
(3cTa GdXfhf(B: 2 / 1796s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs